Nature of Geography Textbook Questions and their Role in Assessment - Mishra, Rishabh Kumar (Asian Journal of Assessment in Teaching and Learning, 2013)
The aim of the present paper is to analyze the nature of textbook-questions and provide its implications for assessment. In India, new geography textbooks were introduced after National Curriculum Framework, 2005. These textbooks comprised in-text as well as end-text exercises and questions. These exercises and questions were analyzed on the basis of content, cognitive level and tools of representation. It was also probed how textbook questions positions learner. Through the rigorous content analysis, both quantitative and qualitative, this paper tries to unfold the epistemological meaning and pedagogical implications of textbook questions.